Enantiomerically Pure Constrained Geometry Complexes of the Rare‐Earth Metals Featuring a Dianionic N‐Donor Functionalised Pentadienyl Ligand: Synthesis and Characterisation. Issue 68 (17th November 2020) - Münster, Katharina; Fecker, Ann Christin; Raeder, Jan; Freytag, Matthias; Jones, Peter G.; Walter, Marc D.
Abstract: We report the preparation of enantiomerically pure constrained geometry complexes ( cgc ) of the rare‐earth metals bearing a pentadienyl moiety (pdl) derived from the natural product (1 R )‐(−)‐myrtenal. The potassium salt 1, [Kpdl*], was treated with ClSiMe2 NH t Bu, and the resulting pentadiene 2 was deprotonated with the Schlosser ‐type base KO t Pen/ n BuLi ( t Pen=CMe2 (CH2 Me)) to yield the dipotassium salt [K2 (pdl*SiMe2 N t Bu)] (3 ). However, 3 rearranges in THF solution to its isomer 3' by a 1, 3‐H shift, which elongates the bridge between the pdl and SiMe2 N t Bu moieties by one CH2 unit. This is crucial for the successful formation of various monomeric C 1 ‐ or dimeric C 2 ‐symmetric rare‐earth cgc complexes with additional halide, tetraborohydride, amido and alkyl functionalities. All compounds have been extensively characterised by solid‐state X‐ray diffraction analysis, solution NMR spectroscopy and elemental analyses. Abstract : Proton migration as key to success . A 1, 3‐H shift enables the synthesis of the first enantiomerically pure pentadienyl‐based constrained geometry complexes, which can be further functionalised to silyamido and alkyl compounds.